2009
DOI: 10.1002/clen.200900059
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Phosphorus Speciation in Pilot Scale Subsurface Flow Wetlands Constructed with Blast Furnace Slag and Gravel

Abstract: Variations in phosphorus (P) speciation were compared for two types of pilot scale wetlands: a blast furnace slag-based constructed wetland (SCW), and a gravel-based constructed wetland (GCW). Synthetic secondary effluent was used as the influent of the wetlands, which contained 1.1 mg/L P with more than 95% present as soluble reactive P (SRP). However, dissolved organic phosphorus (DOP) and particulate phosphorus (PP) emerged in the water along both wetlands. The levels of these three P species varied between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…According to Fig. 2C, the Oc-P content was highest for seven forms of P. Our results agreed with Shan et al (2009), who found that the Oc-P was the most abundant form of P in the sediment. Ca-P content was shown in Fig.…”
Section: The Different P Forms In the Rhizosphere Of Wetland Plantssupporting
confidence: 95%
“…According to Fig. 2C, the Oc-P content was highest for seven forms of P. Our results agreed with Shan et al (2009), who found that the Oc-P was the most abundant form of P in the sediment. Ca-P content was shown in Fig.…”
Section: The Different P Forms In the Rhizosphere Of Wetland Plantssupporting
confidence: 95%
“…Some industrial waste materials, including fly ash, have already been tested as support matrix components of CWS [242,[274][275][276][277][278][279][280], although the target of the treatment systems have been mostly nutrients and other inorganic pollutants such as metals. Still, some of these support materials seemed adequate for the development of the biotic CWS components.…”
Section: Industrial and Agricultural Wastes And By-productsmentioning
confidence: 99%
“…They had been used in the treatment of various wastewaters, such as municipal sewage [1], domestic wastewater [2,3], secondary effluent [4], industrial effluents [5], agricultural wastewater [6], and landfill leachate [7].…”
Section: Introductionmentioning
confidence: 99%